The CASE as a Device of School Practices - Ramírez-Casas del Valle, Lorena (2019)
In the last 15 years, the Chilean educational system has created new normative and legal bodies to furthering inclusion, avoid discrimination, and improve school coexistence. These laws directly address schools, which, from their own translations, also generate their own educational practices. The objective of this research was to comprehend how schools translate and articulate these policies. Through an ethnography of devices (Sisto y Zelaya, 2013),interviews and observations took place in two schools that have a specific team of professionals to articulate these policies. The results show that, from the practices of the teams, a device called CASE emerges as a result; this device is an expression that both schools need and is related to students who have behavioralor learning problems. The CASE, as a device, organizes the teams work, mainly around the detection and support of students, evidence gathering, and safeguards facing the audit. The discussions revolve around the scope of this device and the effects it generates in the school community.